Giftedness: A Three Way Approach and the role of ICTs - Galitskaya, Viktoriya; Batzaka , Maria; Kasapoglou, Efthimios; Drigas, Athanasios (Technium Social Sciences Journal, 2022)
This article presents a group of students who are found in the general classroom. This group consists of gifted children, whose way of learning has not been extensively studied. High achievement students have more developed skills than their peers and this often results in them not engaging in school lessons as they seem too simplistic. This article first introduces the different levels of intelligence that have been formulated from time to time. Secondly, studies showing the relationship between working memory and giftedness, are presented. Finally, ways of teaching giftedness students are suggested with the use of ICTs.